Poland in the Emerging Bipolar World - Sierpowski, Stanisław (Sensus Historiae, 2021)
This article is another attempt to look at the situation of Poland in the conditions of the formation of bipolar politics, the birth of which I situate in the last months of the First World War and associate with revolutions in Russia and the conclusion of separatist peace. The events of 1938, linked to the policy of the Polish Government towards Lithuania and Czechoslovakia, were an important signal of its ambitions to seek a place on the pre-war European arena. The tragic situation of the country attacked from two sides did not-at the behest of Great Britain and France-meet with any reaction in the League of Nations. This was the sign of the inclusion of Polish affairs in the mechanisms of European as well as-to an increasing extent-worldly politics. At the turn of 1941 and 1942, military element became predominant in redefined bipolar politics, which in the overall calculation placed Poland in an unfavourable position. Its military effort did not play the role for which the Polish governments in exile had hoped. On the other hand, the importance of the Eastern Front, whose offensive weighed heavily on the perception of the fate of Central and Eastern Europe by the leaders of Great Britain and the United States, increased immeasurably. The Union of Soviet Socialist Republics pursued its plans, which undoubtedly referred to the Tsarist times, without any major diplomatic difficulties. Given the history of the Baltic states, independent until the Second World War, it can be said with a high degree of probability that the prospect of an analogous fate for Poland would not have been a source of global conflict.